Risk of Coinfection Outbreaks in Temporal Networks: A Case Study of a Hospital Contact Network - Rodríguez, Jorge P.; Ghanbarnejad, Fakhteh; Eguíluz, Víctor M. (Frontiers in Physics, 2017)
We study the spreading of cooperative infections in an empirical temporal network of contacts between people, including health care workers and patients, in a hospital. The system exhibits a phase transition leading to one or several endemic branches, depending on the connectivity pattern and the temporal correlations. There are two endemic branches in the original setting and the non-cooperative case. However, the cooperative interaction between infections reinforces the upper branch, leading to a smaller epidemic threshold and a higher probability for having a big outbreak. We show the microscopic mechanisms leading to these differences, characterize three different risks, and use the influenza features as an example for this dynamics.